Response rates and durability of chemotherapy among 62 patients with metastatic Merkel cell carcinoma. (19th July 2016) - Iyer, Jayasri G.; Blom, Astrid; Doumani, Ryan; Lewis, Christopher; Tarabadkar, Erica S.; Anderson, Austin; Ma, Christine; Bestick, Amy; Parvathaneni, Upendra; Bhatia, Shailender; Nghiem, Paul
Abstract: Cytotoxic chemotherapy is commonly used to treat advanced Merkel cell carcinoma (MCC). However, its efficacy in distant metastatic MCC patients is unclear, in part because most prior reports aggregated these patients with those receiving adjuvant chemotherapy and combined chemoradiation for whom prognosis and outcomes may differ. In this retrospective study, we analyzed detailed records from 62 patients with distant metastatic MCC treated with cytotoxic chemotherapy. Efficacy outcomes including response rate (RR), durability of response (DOR), progression‐free survival (PFS), and overall survival (OS) were evaluated. In this cohort, platinum plus etoposide was the most commonly used first‐line regimen (69%). RR to first‐line chemotherapy was 55% (34/62) with complete responses (CR) in 13% (8/62) and partial responses (PR) in 42% (26/62) while 6% (4/62) had stable disease and 39% (24/62) had progressive disease. Median PFS was 94 days and median OS was 9.5 months from start of chemotherapy. Among responding patients ( n = 34), median PFS was 168 days and median DOR was 85 days. Among 30 of the 62 patients who received second‐line chemotherapy, RR was 23% (7/30; 1 CR, 6 PR), median PFS was 61 days, and median DOR was 101 days. In summary, first‐line chemotherapy is associated with a high RR in metastatic MCC, but responses are typically not durable, and the median PFS is only 3 months. These results suggest rapid emergence of chemoresistance in MCC tumors, and may serve as a useful comparator for immunotherapies currently being explored for metastatic MCC. Abstract : Metastatic Merkel cell carcinoma (MCC) is typically treated with cytotoxic chemotherapy and although 55% of patients initially respond, disease progression occurs in >50% by 3 months and in >90% by 10 months after starting chemotherapy. These data from a large single institutional cohort may serve as a useful comparator for immunotherapies that are currently being explored for metastatic MCC.